2018
DOI: 10.33145/2304-8336-2018-23-442-451
|View full text |Cite
|
Sign up to set email alerts
|

VITAMIN D CONTENT IN POPULATION OF RADIOLOGICALLY CONTAMINATED AREAS IN CHERNIVTSI OBLAST (pilot project)

Abstract: Мета: вивчити статус вітаміну D у населення Чернівецької області, що проживає на радіоактивно забруднених територіях. Матеріали і методи: в одномоментному дослідженні (пілотний проект) в літню пору обстежено 180 осіб віком від 19 до 78 років, які постійно проживають у трьох регіонах Чернівецької області (с. Киселів Кіцманського району, яке віднесено до ІІІ зони радіаційного забруднення внаслідок Чорнобильської катастрофи, а також м. Чернівці і м. Вижниця). Визначення рівня 25(OH)D у сироватці крові обстежених … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 15 publications
1
4
0
9
Order By: Relevance
“…Interestingly, it was found that chronic exposure to IR affected the vitamin D 3 active form level and caused modifications of enzymes involved in vitamin D metabolism [190]. In accordance with this study, Kaminskyi et al [191] described significantly lower vitamin D concentrations among the populations of radiologically contaminated regions of Chernivtsi oblast due to the Chornobyl catastrophe, compared to those in the uncontaminated Ukrainian cities of Charnivtsi and Vyzhnytsia. Therefore, the deficiency of vitamin D in patients during radiotherapy or in medical professionals chronically exposed to low IR doses should be taken into consideration in further research on the supplementary treatment.…”
Section: Vitamin D-function and Antioxidant Effectsupporting
confidence: 81%
“…Interestingly, it was found that chronic exposure to IR affected the vitamin D 3 active form level and caused modifications of enzymes involved in vitamin D metabolism [190]. In accordance with this study, Kaminskyi et al [191] described significantly lower vitamin D concentrations among the populations of radiologically contaminated regions of Chernivtsi oblast due to the Chornobyl catastrophe, compared to those in the uncontaminated Ukrainian cities of Charnivtsi and Vyzhnytsia. Therefore, the deficiency of vitamin D in patients during radiotherapy or in medical professionals chronically exposed to low IR doses should be taken into consideration in further research on the supplementary treatment.…”
Section: Vitamin D-function and Antioxidant Effectsupporting
confidence: 81%
“…Попри певні відмінності в лабораторних підходах, які використовуються для визначення порогової величини D та його дефіциту в різних країнах, очевидним є той факт, що практично в усіх регіонах світу реєструються субоптимальні рівні 25(ОН)D у широких верств населення. Зокрема, гіповітаміноз D є більш вираженим взимку в усіх вікових групах жителів Азії [9,10], Європи [11,12], Латинської Америки [13], Близького Сходу [14], Північної Америки [15] та Океанії [16].…”
unclassified
“…Фактори середовища життєдіяльності також можуть бути причиною захворювань ЩЗ, у тому числі й гіпотиреозу. Відомо, що дефіцит селену та йоду в організмі людини, генетична схильність, несприятливі соціальні (стрес, куріння, алкоголь тощо) та інші чинники сприяють розвитку тиреоїдних патологічних станів [5][6][7][8][9]. У свою чергу, гіпотиреоз може бути причиною розвитку інших захворювань, зокрема серцево-судинної системи [10][11][12][13][14], органів чуття, нервової системи, ожиріння тощо [6].…”
unclassified